Balancing sustainability factors in the implementation of digital libraries for Malay manuscripts: a framework proposal / Nor Hasni Che Hassan, Wan Satirah Wan Mohd Saman and Norshila Shaifuddin - Che Hassan, Nor Hasni; Wan Mohd Saman, Wan Satirah; Shaifuddin, Norshila (Faculty of Information Management, 2023)
This paper aims to explore and understand the factors that affects the implementation of Digital Libraries of Malay Manuscript in libraries. It discusses the issues related to the risk management of digital resources in Malaysian documentary heritage institutions. The study employed a descriptive-qualitative approach to explore how the DLMM is operated in five selected information institutions in Malaysia. Three types of data collection techniques were used: interviews, observation, and document analysis. Fourteen informants were interviewed likely using a semi-structured approach with open-ended questions and probes to gather qualitative data. At same time field observation was done during the same period as the interviews, suggesting that researchers observed realworld situations or events related to their research topic and documents were collected from the annual reports, standard or guide and ICT meeting report/management meeting. The research findings and discovery are significant in highlighting the crucial elements which need to be addressed to ensure the sustainability and successful implementation of any digitization project.